Incitations Fiscales, Opportunisme des Dirigeants et Investissement Dans Les Entreprises au Cameroun - Mfopain Aboubakar; Sadjo Kaoutoing; Mai Django Wambe Thérèse (Journal of Accounting and Taxation, 2022)
This article sets out to show that the opportunism motive which animates managers of companies at the moment of choosing tax incentives or during the adoption of taxation measures or techniques have an impact on the respect of the taxation engagement taken, emphasized in terms of increase in investment. The interest of such an analysis resides in the fact that she permits to understand if managers’ opportunism in terms of soliciting tax advantages has a real impact on the respect of that tax engagement, thus implying an increase or a slowdown of the investment in Cameroonian enterprises. An analysis based on 269 companies drawn in a haphazard manner from the data base of the National Institute of Statistics (NIS) and according to criteria belonging to a regime of favour or the choice of taxation options, reveal that enterprises having a certain tax culture can manipulate with success their systems or options choices and to respect their tax engagements in terms of investments increase. On the contrary, those that operate tax choices with the only aim to benefit from related tax advantages do not always respect their engagements in accordance with the objective to increase investments on their midst